2021
DOI: 10.26434/chemrxiv-2021-3hwfv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transient Absorption of DNA bases in the gas phase and in chloroform solution: a comparative quantum mechanical study

Abstract: We study the excited state absorption (ESA) properties of the four DNA bases (thymine, cytosine, adenine, and guanine) by different single reference quantum mechanical methods, i.e. equation of motion coupled cluster singles and doubles (EOM-CCSD), singles, doubles and perturbative triples (EOM-CC3), and time-dependent density functional theory (TD-DFT), with the long-range corrected CAM-B3LYP functional. Preliminary results at the Tamm-Dancoff (TDA) CAM-B3LYP level using the maximum overlap method (MOM) are r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…For this reason, there are frequent attempts to calculate ESA features with (quadratic response) time-dependent density functional theory, QR TD-DFT, ,,, which is expected to treat ESA in a satisfactory manner in cases where the higher-order excitation contribution is small; such a situation was indeed revealed especially for low-lying ππ* states in DNA bases. , It was further demonstrated in several TD-DFT studies that the experimentally observed absorption features for a number of π-conjugated oligomers could be displayed in a reasonable manner not only for GSA but also for ESA. ,, However, a recent CASPT2 study on distyrylbenzene ( 2PV ) revealed that the main ESA band contains a significant amount of double excitations . This raised the question of whether the good representation of ESA features by QR TD-DFT in such cases is inherent to the method despite the incomplete configuration description; in fact, this has important implications for the general use of QR TD-DFT for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, there are frequent attempts to calculate ESA features with (quadratic response) time-dependent density functional theory, QR TD-DFT, ,,, which is expected to treat ESA in a satisfactory manner in cases where the higher-order excitation contribution is small; such a situation was indeed revealed especially for low-lying ππ* states in DNA bases. , It was further demonstrated in several TD-DFT studies that the experimentally observed absorption features for a number of π-conjugated oligomers could be displayed in a reasonable manner not only for GSA but also for ESA. ,, However, a recent CASPT2 study on distyrylbenzene ( 2PV ) revealed that the main ESA band contains a significant amount of double excitations . This raised the question of whether the good representation of ESA features by QR TD-DFT in such cases is inherent to the method despite the incomplete configuration description; in fact, this has important implications for the general use of QR TD-DFT for this purpose.…”
Section: Introductionmentioning
confidence: 99%